Phenological observation of Leucojum aestivum L. and determination to some morphological features and current and future potential distribution areas depending on climate change - Sarikaya, Ayse Gul; Kavakli, Seydi Ahmet; Uzun, Almira (Elsevier, 2023)
Leucojum aestivum is a perennial bulbous plant belonging to the Amaryllidaceae family. Climate change causes an increase in the danger of plant species extinction by producing negative effects on biodiversity and geographical distribution of species. In this study, phenological observations were obtained from L. aestivum populations, which are naturally distributed in Bursa Karacabey, then the morphological characteristics were determined. Also, MaxEnt programme was used to determine the current and future potential distribution areas of the L. aestivum populations in terms of climate change. The plant height of L. aestivum was determined to be an average of 60.92 +/- 10.38 cm. The width of the bulbs was 31.30 +/- 6.77 mm on average, and also the mean length was 34.67 +/- 6.22 mm. The mean weight was 21.35 +/- 11.74 g. The mean width of the broad linear leaves is 12.61 +/- 3.50 mm and also 51.53 +/- 15.38 cm for their mean length. The mean width of the white flowers was 22.97 +/- 4.01 mm and mean length was 20.56 +/- 1.80 mm. The mean flower stalk length was found to be 36.62 +/- 17.33 mm. The number of flowers was an average of 5.54 +/- 1.21. The mean anther length was 8.98 +/- 1.01 mm. The mean length of the pistil was found to be 11.93 +/- 0.84 mm. The mean width of the fruits was 20.86 +/- 3.62 mm. The number of fruits was found to be a minimum of 1 and maximum of 7 with an average of 2.12 +/- 1.61. The mean width of the seeds was 6.58 +/- 0.50 mm; and also the number of seeds was found to be at least 1 and at most 26 with an average of 8.16 +/- 4.90. According to the outputs of the two scenarios, which we evaluated as mild or strict, while no situation was present that would endanger the extinction of the species in Turkey over the next 80 years based on the SSP1-2.6 scenario; however serious reductions in the distribution areas of the species based on the SSP5-8.5 scenario. For this reason, in-situ and ex-situ conservation measures should be taken according to the species and their habitat requirements, and it is suggested to impose various conservation based sanctions and restrictions apart from these measures.
Keywords: Botany characteristics; Leucojum aestivum L.; MaxEnt; SSP1-2.6 scenario; SP5-8.5 scenario